Shakespeare Text in A.P. Chekhov (On the Example of the Play "The Seagull") - Nizamutdinov T.M. (Peerian Journals Publishing, 2022)
In this paper, the play by A.P. Chekhov, which is written in the best tradition of W. Shakespeare. A.P. Chekhov in The Seagull, like the English playwright, introduces into the structure of comedy an insert performance, a novice writer
Keywords: stage on stage; decadence; Hamlet conflict; new art form